METODOLOGÍA VIRTUAL Y SUS DIMENSIONES EN ESTUDIANTES DE ESTUDIOS GENERALES DE LA UNIVERSIDAD PRIVADA DE ICA, 2016 - CAMPOS SOBRINO, MORAYMA DEL ROSARIO (2016)
The present research "Virtual methodology and its dimensions in general studies students of the “Universidad Privada de Ica”, during the year 2016", had the general objective of describing how learning resources are used in virtual teaching in general studies students. The type of research was basic with a descriptive design also with a quantitative approach, with a non-experimental and cross-sectional design. The population consisted of a group of 73 students from general studies students, the sampling was probabilistic. The technique used was a survey and the instrument were the questionnaire which was validated through expert judgments through the statistician (Cronbach's Alpha). The following conclusions were reached, it was demonstrated that the predominant dimension of virtual methodology in general studies students of the “Universidad Privada de Ica” during 2016 was virtual collaboration, referring to specific objective 1 it was demonstrated that the predominant indicator was access to digital learning resources with a range of 57.5%. The second specific objective obtained a percentage of 50.7%, in a range of good level and with respect to the 3rd specific objective in relation to virtual collaboration was the adaptation to their learning rhythms with a high range of the level of virtual collaboration, it is observed that 5.5% of students consider that the level is bad, 47.9% state that it is regular and 46.6% indicate that the level is good. Therefore, there is a majority tendency of students to consider that the level of virtual collaboration is regular. Keywords: Virtual methodology, learning resources, virtual accompaniment, virtual collaboration.